Using the RADEC Learning Model to Promote Higher Order Thinking Skills (HOTS) in Arabic Language Learning among Grade 8 Students at As-Salam Middle School for Quran Memorization Bogor - Etri Suryanti; Eva Lathifah Fauzia; Acep Hermawan (UIN Sunan Gunung Djati Bandung, 2025)
The challenges of 21st century education require students to have critical, analytical, and creative thinking skills, which are classified as high-level thinking skills. However, Arabic language learning at As-Salam Qur'an Junior High School in Bogor is still dominated by memorization methods and basic knowledge and skills. This is the background of the low level of thinking skills of students. Therefore, an innovative learning model is needed to improve students' high-level thinking skills, one of which is the RADEC (Read, Answer, Discuss, Explain, Create) learning model. The purpose of this study is to examine the application of the RADEC model in Arabic language learning and measure its effectiveness in improving students' high-level thinking skills. In addition, this study also aims to compare learning outcomes between classes that use the RADEC model and classes that use the regular learning model. The basic concept of this research is based on the theory of social constructivism which emphasizes the importance of active and collaborative learning. The RADEC model consists of five stages: reading to gain initial understanding, answering questions based on high thinking skills, discussing answers in groups, explaining the results of the discussion in front of the class, and creating new products or solutions based on their understanding. Each stage is designed to develop HOTS skills according to Bloom's revised taxonomic theory, i.e. student analysis, evaluation, and creation. The research method used was a quasi-experimental method with a nonequivalent control group design. Class VIII C as an experimental class and class VIII D as a control class. Data is collected through observation and tests. Data analysis was carried out with the help of IBM SPSS Statistics 29. The results of the study show that the Read stage in the RADEC model in Arabic learning needs to be prepared by the teacher and the RADEC model will be easier to accept if students complete the previous material. The RADEC learning model and the regular learning model are effective in improving students' high-level thinking skills. However, the average posttest score of the experimental class was higher than that of the control class, with the N-Gain test result of 0.5057 for the experimental class and 0.03834 for the control class. Statistical tests showed that there was a significant difference between the learning outcomes of the two classes. The conclusion of this study is that the RADEC model can be used as an alternative innovative learning model to improve students' HOTS in Arabic language learning.